The effect of training using an electromechanical-optical device designed to improve the speed and accuracy of scoring for advanced Futsal footballers - Ali Majeed Zayer, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research was demonstrated by applying exercises through the use of an electro-mechanical-optical device designed to develop the speed and accuracy of scoring for futsal players. The problem lies in the question: Does training using the optical electro-mechanical device designed to develop the speed and accuracy of scoring among futsal players work for advanced players?The aim of the research was to design an electromechanical optical device to develop the speed and accuracy of scoring and to prepare exercises through the device and to identify their effect. The researcher used the experimental approach in the method of equal groups. The researcher conducted two exploratory experiments (for exercises and for testing), as well as applying the scientific foundations to the test, and the researcher applied the exercises on the device for a period of (10) weeks at a rate of (3) units per week with a total of (30) training units, and after data collection and treatment appeared statistically An improvement in the speed and accuracy of scoring; the researcher concluded that the exercises with the help of the designed electromechanical device contributed to the development of the time and accuracy of scoring for the research sample. The designed device had a positive impact on players' development.